A heat-resistant organic adhesive for joining Al2O3 ceramics in air and argon atmospheres. (April 2017) - Wang, Xiaozhou; Wang, Jun; Wang, Hao
Abstract: An organic adhesive for joining Al2 O3 ceramics was prepared by using a precursor as a matrix, with B4 C and SiO2 additives. The resulting adhesive was characterised by a shear strength test, thermogravimetry-differential scanning calorimetry (TG-DSC), Fourier transform-infrared (FT-IR), X-ray diffraction (XRD), and scanning electron microscopy (SEM) analyses. The bonded Al2 O3 joints were found to exhibit high shear strengths (over 10 MPa) after heat treatment at a temperature of 200 °C to 1200 °C in either an air or Ar atmosphere. In an argon atmosphere, the B4 C and SiO2 act as inert fillers. The satisfactory bonding strengths of the Al2 O3 joints mainly result from the outstanding adhesive properties of the precursor matrix. In air, the B4 C is converted to B2 O3 above 500 °C and reacts with SiO2 to form a borosilicate phase. The formation of B2 O3 and borosilicate glass reduces the volume shrinkage of the adhesive, improves the densification of the bonding layer and enhances the interface joining force, which we believe are responsible for the high shear strengths of the Al2 O3 joints (over 40 MPa). The high strength and high-temperature resistance enable the application of the adhesive to the joining of ceramic materials for practical applications.